Impact of Innovation Leadership on Supply Chain Efficiency: The Role of Process Improvement - Purwoko, Purwoko; Hassan, Zainudin Bin (Universitas Muhammadiyah Yogyakarta, 2023)
Research aims: This research aims to determine the influence of innovation leadership on supply chain efficiency mediated by process improvement.Design/Methodology/Approach: The objects of this research were micro, small, and medium enterprises (MSMEs) players in the creative economy sector in the Yogyakarta Special Region, Indonesia. Measurements of the outer model, inner model, and hypothesis testing (directly and indirectly) were carried out on the data sample of MSME actors in the creative economy sector in Yogyakarta Special Region utilizing the SmartPLS statistical tool. The sampling employed purposive sampling with a total sample size of 267 creative economy MSMEs.Research Findings: The results uncovered that innovation leadership positively affected supply chain efficiency, implying that innovation leadership could significantly improve supply chain efficiency. Innovation leadership also positively influences process improvement, showing that if the innovation leadership is good, process improvement will increase significantly. In addition, process improvement positively impacted supply chain efficiency, indicating that process improvement could significantly improve supply chain efficiency. Lastly, process improvement could mediate the effect of innovation leadership on supply chain efficiency significantly, denoting that process improvement has a highly important role in improving supply chain efficiency. Theoretical Contribution/Originality: This study indicates that innovative leaders are highly important in improving their supply chain efficiency, and process improvement as a mediating variable, a novelty in this study, has a very significant role for innovative leaders in improving supply chain efficiency.Practitioners/Policy Implications: Creative economy MSMEs must become innovative leaders in their businesses to increase efficiency in the supply chain. In addition, MSMEs need to continuously improve their business processes, especially in the supply chain.Research Limitations/Implications: The independent variable in this research was only one, i.e., innovation leadership, so it is less comprehensive. To be more comprehensive, other independent variables, such as intellectual capital or moderating variables of government policies, can be added.